2016
DOI: 10.1038/srep36029
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Insulin/Glucose Model after a Mixed-Meal Test in Patients with Type 1 Diabetes on Insulin Pump Therapy

Abstract: Current closed-loop insulin delivery methods stem from sophisticated models of the glucose-insulin (G/I) system, mostly based on complex studies employing glucose tracer technology. We tested the performance of a new minimal model (GLUKINSLOOP 2.0) of the G/I system to characterize the glucose and insulin dynamics during multiple mixed meal tests (MMT) of different sizes in patients with type 1 diabetes (T1D) on insulin pump therapy (continuous subcutaneous insulin infusion, CSII). The GLUKINSLOOP 2.0 identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…It has been reported that the onset of most type 1 diabetes is related to insulin production deficiency and injury of islet tissues (40,41). Type 1 diabetes results from a chronic autoimmune process continuing for years after presentation (42).…”
Section: Hbxip Participates In the Transcription Of Insulinmentioning
confidence: 99%
“…It has been reported that the onset of most type 1 diabetes is related to insulin production deficiency and injury of islet tissues (40,41). Type 1 diabetes results from a chronic autoimmune process continuing for years after presentation (42).…”
Section: Hbxip Participates In the Transcription Of Insulinmentioning
confidence: 99%
“…This problem is often formulated in the form of least squares, as in models related to diabetes [10,19,20], biological pathways [21][22][23][24], and pharmacokinetics/pharmacodynamics [25,26]. Least squares problems may arise in statistical regression as well [27][28][29][30][31][32].…”
Section: Least Squares Methodsmentioning
confidence: 99%
“…For instance, the parameters may represent biological rates or physical quantities that cannot be negative or that are admissible only inside a specific interval. In other cases, the value of certain parameters may depend on other parameters, as in the case when their sum should be smaller or equal to a certain threshold [10]. We refer to the space where the parameters θ can vary, according to constraints, as the space of parameters.…”
Section: Model Tuning and Biomarker Identification As Global Optimizamentioning
confidence: 99%
“…In this context, a number of mathematical models of glucose and insulin dynamics have been developed to allow the description and interpretation of such processes, which are often not accessible to direct measurement in vivo [ 5 ]. These models usually apply ordinary differential equations (ODEs) or delay differential equations (DDEs) to describe the physiology of the glucose-insulin system in different experimental conditions and with varying degrees of detail [ 6 14 ]. Originally built upon the parsimony principle in order to soften the complexity of experimental protocols and computational efforts, the first modeling milestone is represented by the so called “minimal model” [ 8 ], which was originally applied to estimate insulin sensitivity by inspecting the time courses of insulin and glucose after an intravenous glucose tolerance test (IVGTT).…”
Section: Introductionmentioning
confidence: 99%